Heritage, Thrift and our Children's Children - Sarah May (Cultural Heritage and the Future, 2019)
Heritage is commonly claimed to preserve things from the past for future generations. What does the word ‘generations’ do in that phrase? It reminds us of children, so that the phrase becomes analogous to ‘for our children, and our children’s children’. Of course, the children of today are the adults of tomorrow, so what is at stake when we use this formulation? This paper will explore the role of children in heritage discourse as placeholders of the future. It will examine how this role exerts a domesticating force for the future which twins with the rescuing of the past to avoid anxieties about the present.